Pathophysiology of swallowing following oropharyngeal surgery for obstructive sleep apnea syndrome. Issue 5 (21st December 2017) - Schar, M.; Woods, C.; Ooi, E. H.; Athanasiadis, T.; Ferris, L.; Szczesniak, M. M.; Cock, C.; Omari, T.
Abstract: Background: Uvulopalatopharyngoplasty (UPPP) and coblation channeling of the tongue (CCT) are oropharyngeal surgeries used to treat obstructive sleep apnea syndrome. The extent to which UPPP and CCT affect pharyngeal swallow has not been determined. We therefore conducted a novel case series study employing high‐resolution impedance manometry (HRIM) to quantify the swallowing‐related biomechanics following UPPP and/or CCT surgery. Methods: Twelve patients who underwent UPPP+CCT or CCT only were assessed an average 2.5 years postsurgery. Swallow function data were compared with ten healthy controls. All patients completed the Sydney swallow questionnaire (SSQ). Pharyngeal pressure‐flow analysis of HRIM recordings captured key distension, contractility and pressure‐flow timing swallow parameters testing 5, 10, and 20 mL volumes of thin and thick fluid consistencies. Key Results: Postoperative patients had more dysphagia symptoms with five returning abnormal SSQ scores. Swallowing was biomechanically altered compared to controls, consistent with diminished swallowing reserve, largely driven by elevated hypopharyngeal intrabolus pressure due to a reduced capacity to open the upper esophageal sphincter to accommodate larger volumes. Conclusions & Inferences: Patients who have undergone UPPP and/or CCT surgery appear to have a deficiency in normal modulation of the swallowing mechanism and a reduced swallowing functional reserve. We speculate that these changes may become relevant in later life with the onset of age‐related stressors to the swallowing mechanism. This case series strikes a note of caution that further studies are needed to determine the role of preoperative swallow assessment in patients undergoing UPPP and/or CCT surgery. Abstract : In some patients, oropharyngeal surgery causes dysphagia, the pathophysiology of swallowing in this context is not understood. Swallow function is described for a case series of patients postoropharyngeal surgery. Oropharyngeal surgery patients had reduced swallowing reserve due to impaired swallow response to volume challenge.